The exiles [videorecording (DVD)] - Choy, Christine; Kaixi, Wu're; Yan, Jiaqi, 1942- (Gravitas Ventures, 2022)
Documentary filmmaker, Christine Choy, tracks down three exiled dissidents from the Tiananmen Square massacre in order to find closure on an abandoned project she began shooting in 1989.